Kinetic studies of copper-catalysed conjugate addition reactions with organoaluminium reagents and their implementation towards enantioselective synthesis of quinolone derivatives - Kingsbury, A. (2019)
Conjugate addition reactions with organometallic reagents have been extensively utilised in the synthesis of a wide range of diverse molecules. Despite this, certain phenomena regarding the mechanistic pathway of the reaction remain unexplored. As such, challenges associated with certain synthetic transformations involving this class of reaction require extensive research to expand our understanding on a molecular level and implement this understanding in a functional capacity.